2007
DOI: 10.1016/j.ygeno.2006.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Obscurin-like 1, OBSL1, is a novel cytoskeletal protein related to obscurin

Abstract: Cytoskeletal adaptor proteins serve vital functions in linking the internal cytoskeleton of cells to the cell membrane, particularly at sites of cell-cell and cell-matrix interactions. The importance of these adaptors to the structural integrity of the cell is evident from the number of clinical disease states attributable to defects in these networks. In the heart, defects in the cytoskeletal support system that surrounds and supports the myofibril result in dilated cardiomyopathy and congestive heart failure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
94
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 41 publications
2
94
1
Order By: Relevance
“…The major function of this new protein might therefore be structural, possibly adding an additional layer of crosslinks between myosin filaments. During the preparation of this manuscript, Obsl1 was described as a protein of the M-band, Z-disk, intercalated disk, nuclear lamina and cytosol (Geisler et al, 2007). The antibodies purified for this study, however, show marked M-band localization, which is only disrupted by the dominant-negative effects of myomesin, titin or the binding domains to these on Obsl1 itself (supplementary material Fig.…”
Section: Obscurin and Obscurin-likementioning
confidence: 93%
See 1 more Smart Citation
“…The major function of this new protein might therefore be structural, possibly adding an additional layer of crosslinks between myosin filaments. During the preparation of this manuscript, Obsl1 was described as a protein of the M-band, Z-disk, intercalated disk, nuclear lamina and cytosol (Geisler et al, 2007). The antibodies purified for this study, however, show marked M-band localization, which is only disrupted by the dominant-negative effects of myomesin, titin or the binding domains to these on Obsl1 itself (supplementary material Fig.…”
Section: Obscurin and Obscurin-likementioning
confidence: 93%
“…Furthermore, we identified novel splice variants of Obsl1 that lack the N-terminal domains responsible for titin and myomesin interaction. It is possible, therefore, that the puzzlingly complex picture of Obsl1 localization observed by Geisler et al (Geisler et al, 2007) relates to those isoforms lacking the M-band-targeting domains 1-3.…”
Section: Obscurin and Obscurin-likementioning
confidence: 98%
“…OBSL1 is closely related to the giant muscle protein obscurin (Geisler et al 2007) and has been found to interact physically with the other muscle proteins titin and myomesin (Fukuzawa et al 2008). However, 3-M syndrome is not recognised as a disease of muscular defects, suggesting that OBSL1 is not primarily a muscle protein.…”
mentioning
confidence: 99%
“…Hanson et al (2009) postulated that CUL7 and OBSL1 are likely components of a common pathway because pathogenic mutations in both genes cause 3-M syndrome and that loss of OBSL1 by siRNA knockdown also led to reduction in CUL7 expression. Geisler et al (2007) suggested that OBSL1 is a putative cytoskeletal adaptor protein; therefore, it is possible that OBSL1 acts to facilitate the assembly of the CUL7-SCF complex. CCDC8 is a protein of unknown molecular function; however, we have found that OBSL1 interacts with both CUL7 and CCDC8, suggesting that all three proteins are components of the same molecular pathway (Hanson et al 2011).…”
mentioning
confidence: 99%
“…Various mutations in genes encoding for ID proteins have been causatively linked to these complex disorders, many of which manifest themselves as ARVC; (recently reviewed in Protonotarios et al, 2011). There are ~200 known proteins that are associated with the ID (Dowling et al, 2008;Estigoy et al, 2009;Geisler et al, 2007;Lin et al;Kargacin et al, 2006;Satomi-Kobayashi et al, 2009;www.intechopen.com Cardiomyopathies -From Basic Research to Clinical Management 248 Schroen et al, 2007;Seeger et al, 2010). Herein, we provide a summation of the current knowledge on the junctional structures present in the ID, focusing on their most prominent and influential components, and how these relate to each other and the sarcomeric cytoskeleton in normal and disease states.…”
mentioning
confidence: 99%